Deciphering the Translational Strategies of Nanotechnology in Bacterial Conjunctivitis: Looking Ahead - Devender; Ritu; Quadri, Khushi; Rani, Laxmi; Mathur, Pooja (Recent Advances in Anti-Infective Drug Discovery, 2025)
Bacterial conjunctivitis is a common eye infection caused by bacteria, posing significant treatment challenges due to rising antibiotic resistance and the limitations of traditional therapies. Standard treatments, including topical antibiotics, often suffer from issues such as poor bioavailability, limited effectiveness, and patient adherence. Nanotechnology offers an innovative approach, providing potential solutions for more effective drug delivery, diagnostics, and therapeutic interventions. The objective of this study is to explore the role of nanotechnology in improving the management of bacterial conjunctivitis. Specifically, it examines how nanostructured drug carriers, such as nanoparticles, nanogels, and liposomes, can enhance ocular drug delivery and therapeutic outcomes. A key focus is on the influence of the hydrodynamic radius (Rh) in optimizing stability, solubility, and bioavailability. Nanotechnology has shown promise in improving the delivery of drugs for bacterial conjunctivitis by enhancing ocular penetration and prolonging the release of active agents. The hydrodynamic radius (Rh) of nanoparticles plays a critical role in stabilizing the colloidal structure of the formulation, preventing aggregation and sedimentation. Furthermore, optimizing Rh can increase the surface area-to-volume ratio, which is beneficial for improving the solubility of poorly soluble drugs, thereby enhancing their bioavailability. Nanotechnology-based systems can also enable the development of diagnostic tools, such as nanosensors, capable of quickly and accurately detecting bacterial pathogens, facilitating timely, targeted treatments and reducing unnecessary use of broad-spectrum antibiotics. The precise control of nanoparticle Rh enhances drug stability, bioavailability, and sustained release, ultimately improving patient compliance and therapeutic efficacy. The future of bacterial conjunctivitis treatment is promising, with further research focused on optimizing nanoparticle characteristics such as size, surface modification, and targeted drug delivery. However, challenges remain, particularly concerning the safety of nanoparticles, including potential risks to ocular tissues and long-term effects. Continued research, including <span class=
Keywords: nanosensors